Depletion of tet2 results in age-dependent changes in DNA methylation and gene expression in a zebrafish model of myelodysplastic syndrome - Neelamraju, Yaseswini; Gjini, Evisa; Chhangawala, Sagar; Fan, Hao; He, Shuning; Jing, Chang-Bin; Nguyen, Ashley T.; Prajapati, Subhash; Sheridan, Caroline; Houvras, Yariv; Melnick, Ari; Look, A. Thomas; et al. (Frontiers in Hematology, 2023)
Myelodysplastic Syndrome (MDS) is a heterogenous group of clonal hematopoietic disorders characterized by ineffective hematopoiesis, cytopenias and dysplasia. The gene encoding Ten-eleven translocation 2 (TET2), a dioxygenase enzyme that catalyzes the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine, is a recurrently mutated tumor suppressor gene in MDS and other myeloid malignancies. Previously, we reported a stable zebrafish line with a loss-of-function mutation in the tet2 gene. The tet2m/m mutant zebrafish developed a pre-MDS state with kidney marrow dysplasia but normal circulating blood counts by 11 months of age and accompanying anemia signifying the onset of MDS by 24 months of age. In the current study, we collected progenitor cells from the kidney marrows of the adult tet2m/m and tet2wt/wt fish at 4 and 15 months of age and performed enhanced reduced representation of bisulphite sequencing (ERRBS) and bulk RNA-seq to measure changes in DNA methylation and gene expression of hematopoietic stem and progenitor cells (HSPCs). A global increase in DNA methylation of gene promoter regions and CpG islands was observed in tet2m/m HSPCs at 4 months of age when compared to the wildtype. Further, hypermethylated genes were significantly enriched for targets of SUZ12 and MTF2 - involved in polycomb repressive complex 2 (PRC2). However, between 4 and 15 months of age, we observed a paradoxical global decrease in DNA methylation in tet2m/m HSPCs. Gene expression analyses identified upregulation of genes associated with mTORC1 signaling and interferon gamma and alpha responses in tet2m/m HSPCs at 4 months of age when compared to the wildtype. Downregulated genes in HSPCs of tet2 mutant fish at 4 months of age were enriched for cell cycle regulation, heme metabolism, and IL2/STAT5 signaling, possibly related to increased self-renewal and clonal advantage in HSPCs with tet2 loss of function. Finally, there was an overall inverse correlation between overall increased promoter methylation and gene expression.